Gotong Royong Sebagai Nilai Community Engagement Pada Masyarakat Tani Di Desa Belanti Siam, Kecamatan Pandih Batu, Kabupaten Pulang Pisau, Kalimantan Tengah - Zulkifli Abdullah; Bahrianoor Bahrianoor; Irwani Irwani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Belanti Siam Village is one of the villages in Pandih Batu District, Pulang Pisau Regency, Central Kalimantan, this village is the target of the food estate program policy by the central government. Based on the design of the policy program, it was noted that Belanti Village has a rice planting potential of around 80% compared to the surrounding villages. In addition, Belanti Village also has many farmer groups who are members of the Association of Farmers Groups as the basis for a safety net as well as social power for farmers to increase their productivity. Gotong royong as the value of community engagement is an approach used in understanding the pattern of empowerment of rural communities as well as being the basis of strength in managing and utilizing their agricultural potential amidst the economic limitations that plague them. Through a qualitative method with a descriptive approach, this study seeks to describe as well as interpret the social practices of the farming community in Belanti Siam Village. As a result, the people of Belanti Siam Village are a society with strong values of solidarity and solidity. On that basis, the people of Belanti Siam Village plan and implement their work together. Starting from cleaning the fields, planting rice seeds, to harvesting is done in mutual cooperation. It didn't stop there, they also worked hand in hand to empower local people who did not have rice fields to help people who had rice fields and were then given wages.